Non-exhaust vehicle emissions of particulate matter and VOC from road traffic: A review. (1st October 2021) - Harrison, Roy M.; Allan, James; Carruthers, David; Heal, Mathew R.; Lewis, Alastair C.; Marner, Ben; Murrells, Tim; Williams, Andrew
Abstract: As exhaust emissions of particles and volatile organic compounds (VOC) from road vehicles have progressively come under greater control, non-exhaust emissions have become an increasing proportion of the total emissions, and in many countries now exceed exhaust emissions. Non-exhaust particle emissions arise from abrasion of the brakes and tyres and wear of the road surface, as well as from resuspension of road dusts. The national emissions, particle size distributions and chemical composition of each of these sources is reviewed. Most estimates of airborne concentrations derive from the use of chemical tracers of specific emissions; the tracers and airborne concentrations estimated from their use are considered. Particle size distributions have been measured both in the laboratory and in field studies, and generally show particles to be in both the coarse (PM2.5-10 ) and fine (PM2.5 ) fractions, with a larger proportion in the former. The introduction of battery electric vehicles is concluded to have only a small effect on overall road traffic particle emissions. Approaches to numerical modelling of non-exhaust particles in the atmosphere are reviewed. Abatement measures include engineering controls, especially for brake wear, improved materials (e.g. for tyre wear) and road surface cleaning and dust suppressants for resuspension. Emissions from solvents in screen wash and de-icers now dominate VOC emissions from traffic in the UK, and exhibit a very different composition to exhaust VOC emissions. Likely future trends in non-exhaust particle emissions are described. Highlights: Non-exhaust particle and VOC emissions now frequently exceed exhaust emissions. Particles are present in both fine and (mainly) coarse fractions. Emissions are quantifiable in the atmosphere through chemical tracers. Mitigation options for emissions reduction are discussed. Likely future trends in emissions are examined.